Social inclusion of athletes with disabilities in regional national teams - Vinokurova D.M.; Gotovtseva E.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the elements that contribute to the inclusion of athletes with disabilities in regional national teams. Methods and structure of the study. To gather empirical information, a survey was created for athletes with disabilities (n=36) who are enrolled in the National Research University of the Russian Federation, the «Republican Center for Sports Training of National Teams of the Russian Federation». This center is responsible for developing and supporting sports training in 13 disciplines. Results and conclusions. By comparing their condition before and after participating in sports, participants note not only an improvement in their well-being and vitality, but also an expansion of their social circle and other activities. In the world of sports, the rules, criteria, and standards are clearly defined, providing a legitimate opportunity for recognition, social status, and more. It is evident that regular training of athletes with disabilities at the Sports Training Center for national teams contributes to their integration not only into the sports arena, where they can become renowned and respected sports masters, winners, or medalists in sports competitions of various levels. The recognition of athletes with disabilities underscores the fact that engaging in sports has given them a sense of belonging to a larger sports community.